Biomolecule nanosensing - Shi, Hui Qing (2018)
This study explored an alternative method of detection of Genetically Modified Organisms (GMOs) in food – the use of electrochemical label in PCR instead of the conventional use of fluorescent label in PCR. Given the various advantages posed by electrochemical detection over fluorescent detection such as its simplicity and inexpensive equipment involved, electrochemical PCR was proposed in this study. Having excellent electrochemical properties, Nano Graphene Oxide (NGO) was studied for its possible use as an electrochemical label, and electrochemical reduction of NGO was examined for its use as the signal transduction event for electrochemical PCR. Covalent conjugation was investigated as the method to attach NGO to the single-stranded DNA (ssDNA) primer modified by an amino group. Hybridisation of the NGO-labelled ssDNA primer with the complementary ssDNA targets was performed to simulate the effect of a labelled PCR amplicon. It was then discovered that both NGO-ssDNA conjugates and NGO-dsDNA hybrids (formed by hybridization of NGO to ssDNA targets) produced electrochemical reduction signal of a lower intensity compared to the initial reduction signal of NGO. This could be attributed to the interference brought by non-covalent interactions between the oxygen functionalities on NGO and the ssDNA. Therefore, it is important to investigate the possible effects of attachment of ssDNA to NGO on the electrochemical reduction signal of NGO. The detection limit of NGO-dsDNA hybrids was then determined to find out the minimum concentration of NGO required to produce NGO-dsDNA hybrid of strong and reproducible signal which is important for future applications for detection of GMOs in food. Since fluorescent PCR requires the use of expensive equipment and labels, this study is important as it provides information regarding the use of a cheaper alternative of electrochemical PCR which is currently not a well-established area of research.